Sources and Cycling of Particulate Organic Matter in Baffin Bay: A Multi-Isotope δ13C, δ15N, and Δ14C Approach - Fox, Aislinn; Walker, Brett D. (Frontiers in Marine Science, 2022)
The Canadian Arctic is warming three times faster than the rest of the planet. The impact of climate change on the Arctic carbon cycle, and in particular for Baffin Bay, remains poorly constrained. Sinking particulate organic matter (POMsink) is a key component of the biological carbon pump and provides a direct linkage between surface productivity and the preservation of carbon in marine sediments. While POMsink provides a rapid POM shunt to the deep ocean (days) the majority of marine POM is suspended (POMsusp) persists for years in the water column. Stable carbon (δ13C), nitrogen (δ15N) and radiocarbon (Δ14C) measurements are powerful tools for evaluating sources and cycling of POM. In this study, we measure depth-integrated (0-400m) POMsusp stable carbon (δ13C), nitrogen (δ15N) and radiocarbon (Δ14C) values at 11 stations in Baffin Bay. We use POM C:Na ratios to evaluate its diagenetic state. POMsusp δ13C and δ15N values ranged from −21.6‰ to −29.5‰, and +3.84‰ to +7.21‰, respectively. POMsusp Δ14C values ranged from −41.8‰ to +76.8‰. Together, our results suggest Baffin Bay POMsusp has multiple carbon and nitrogen sources. POMsusp δ13C and Δ14C are strongly correlated to surface salinity, indicating surface water has a strong influence on POMsusp isotopic composition and 14C-age. POMsusp from coastal Greenland stations have similar Δ14C values to surface dissolved inorganic carbon (DIC) and POM concentrations, consistent with primary production as the predominant POMsusp source in Eastern Baffin Bay. Positive POMsusp Δ14C values in central Baffin Bay suggest an accumulation of atmospheric “bomb” 14C in the sub-polar gyre. POMsusp exiting Davis Strait via the Baffin Island Current was determined to have a significant degraded, resuspended sediment component. Finally, POMsusp δ15N values highlight two distinct N sources in Baffin Bay: Pacific and Arctic nutrients at Northern gateway stations vs. the influx of Atlantic nutrients via Davis Strait along coastal Greenland. Overall, these first Baffin Bay POMsusp Δ14C values provide useful baseline data for rapidly changing Arctic ecosystem.